Prarancangan Pabrik Monosodium Glutamat Dari Molases Dengan Proses FermentasiKapasitas 45.000 Ton/Tahun - Prabowo, Danang Eko, Rois Fatoni,ST., M.Sc (2017)
ABSTRACT Monosodium glutamate factory from molasses with the fermentation process using the bacteria Micrococcus glutamicus with a capacity of 45,000 tons/year it is planned to operate for 330 days/year. This product to meet the needs of home and abroad, and as a goal to optimize raw material a rich molasses. Taking into account the various factors supporting, then factory is planned to be built in Lampung Tengah. Monosodium glutamate produced in fermenters batch. The reaction takes place in the liquid phase, the nature of such an isothermal reaction, with operating conditions at a temperature of 30 ° Cand a pressure of 1 atm. Needs 30,695.76 kg of molasses per hour, and produce monosodium glutamate amounted to 5,681.81 kg per hour. Supporting utilities includes water supply is obtained from the River, water needs 169,923.24 kg per hour, and the provision of 9,709.547 kg of steam per hour gained from boiler with fuel amounted to 104.924 litres per hour, 986.116 kW electricity needs are supplied from PLN and is used as a backup power generator. The factory was founded by the number of employees of 162 people. This form of company is PT (limited liability company) with a land area of 75,500 m2. Monosodium glutamate factory memerluakan fixed capital of Rp 1.456.311.377.220 RP From economic analyses plant profit before tax of Rp RP 171.004.524.539 per year, profit after tax of Rp RP 128.253.393.404 per year. The ROI (Return Of Investment) and 11.7% before tax after tax of 8.8%, POT (Pay Out Time) before tax of the tax year and after 4.60 5.32 years. BEP (Break Even Point) of 58.96%, SDP (Shut Down point) of 23.84% and IRR-DFC (Internal Rate of Return-Discounted Cash Flow) accounting for 18%. Feasibility analysis of the data is summed up this profitable and viableplant established.